Laparoscopic TAPP Single Access Hernioplasty with Simultaneous Appendectomy for Chronic Appendicitis - Parkhomenko, K. Yu. (Journal of Education, Health and Sport, 2020)
Aim. To investigate the technological features and immediate results of simultaneous laparoscopic hernioplasty of inguinal hernia and appendectomy in chronic appendicitis. Methods. Was performed the analysis of the initial data, complications, duration of surgery and hospitalization in patients after simultaneous appendectomy and TAPP inguinal hernia repair in comparison with isolated TAPP. Results. Simultaneous appendectomy during laparoscopic hernioplasty does not significantly affect the performance of TAPP inguinal hernia repair, but it increases the duration of the intervention due to additional manipulations. This does not affect the incidence of complications and the length of hospital stay. Conclusions. Simultaneous laparoscopic appendectomy for TAPP hernioplasty is advisable in patients with chronic appendicitis and inguinal hernias.